MODEL PELIMPAHAN KEWENANGAN BADAN PEMERIKSA KEUANGAN DALAM PELAKSANAAN TUGAS PEMERIKSAAN PENGELOLAAN DAN TANGGUNG KEUANGAN NEGARA - Muhammad Ramadhani; Bahrullah Akbar; Murtir Jeddawi; M. Irwan Tahir (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
This study aims to analyze the problem of how the delegation of authority and the model of delegation of authority that can be developed for the BPK in the implementation of auditing tasks for the management and responsibility of state finances using Koontz and Weihrich's theory regarding the seven principles for transferring authority. The research method used is a qualitative research design with a descriptive approach. The results showed that the transfer mechanism was not fully in line with Law Number 30 of 2014 concerning Government Administration. The obstacle in the implementation of the delegation of authority policy is that the policy design is not in line with the applicable regulations, and it requires commitment from policy makers and policy implementers to adjust policies and policy implementation with the development of laws and regulations and general principles of good governance. The model of delegation of authority suggested by this study in the implementation of auditing tasks for the management and responsibility of state finances is a comprehensive audit task mandate, so that the BPK executor, and examiners and experts outside the BPK perform audit duties for and on behalf of the BPK based on statutory regulations and general principles of good governance.